Analysis of Factors Influencing School Readiness of Children Aged 5-6 Year - Agussalim, Amirah Aminanty; Rasyid, Nurfajriyanti (Universitas Negeri Makassar, 2025)
This study aims to analyze the factors influencing school readiness among children aged 5-6 years in Makassar City. The research employed a quantitative method with a descriptive correlational approach, involving 81 children selected through purposive sampling. The instrument used was the Nijmeegse Schoolbekwaamheids Test (NST), which measures ten domains of school readiness, including cognitive, motor, social, language, and emotional aspects. The results showed that the majority of children (92.5%) were categorized as